Giant placenta chorioangioma with postpartum bleeding and uterine atony. (2nd December 2021) - Castañeda, Maria Carolina; Acero, Nicolás Luna; Samer, Mauricio Manrique; Celis, Mariana Medina; Pardo, Myriam C; Olaya-C, Mercedes
Abstract : Chorioangioma is the most commonly occurring vascular, non-malignant placental tumor in pregnancy, with a reported incidence of 1% in all examined placentas. Nonetheless, real tumor incidence remains unknown because of small specimen sizes, which contributes to a lack of detection throughout the entire gestational period. Prenatal detection and diagnosis may be possible with ultrasound screening; however, most placental chorioangioma diagnoses are postnatal, based upon histopathological studies. This article report the case of postnatal diagnosis and associated complications in a 35-year-old patient with a 6 cm × 4 cm × 4 cm placental chorioangioma.